Reframing patient-centered strategy: why life science organizations need a Chief Patient Officer (CPO) function - Ramiro E Gilardino; Ross Maclean (Journal of Patient Centricity, 2026)
Despite universal adoption of patient centricity rhetoric in life sciences, patient insights remain structurally fragmented across organizational functions and rarely influence enterprise-level decisions. This paper identifies the absence of a unifying capability, not intent or tools, as the root cause, and proposes the Chief Patient Officer (CPO) function as the solution. Defined through five features (lifecycle stewardship, evidence integration, governance and standards, ecosystem activation and translation into decisions), the CPO acts as the organizational ‘owner of coherence’, bridging scientific maturity and healthcare system readiness. The paper contrasts the CPO mandate with existing roles (Chief Medical Officer, medical affairs), presents case studies in precision oncology and multiple sclerosis, and demonstrates measurable return on access investment through quantifiable key performance indicators. As health technology assessment bodies, regulators, and payers increasingly require credible, methodologically rigorous patient evidence, from patient reported outcomes and patient preference studies to real-world evidence and distributional cost-effectiveness analysis, organizations without a structured patient strategy face growing commercial and reputational risk. The CPO function is the missing architectural layer.